THE MODERATING ROLE OF CEO OVERCONFIDENCE IN THE EFFECT OF GREEN INNOVATION ON FIRM VALUE - Paulina Sutrisno; Elphan Agustinus Na Goppies (Faculty of Economics and Business University of Mataram, 2026)
This study examines the effect of green innovation on firm value and investigates whether CEO overconfidence moderates this relationship. The sample consists of 346 non-financial firms listed on the Indonesia Stock Exchange covering the period 2019–2023, yielding 1,730 firm-year observations selected through purposive sampling. The data were analyzed using generalized least squares (GLS) to address potential heteroskedasticity and autocorrelation in the panel data. The findings reveal that green innovation has a positive and significant impact on firm value. However, CEO overconfidence does not moderate the relationship between them. The results suggest that the value-enhancing effect of green innovation is primarily driven by firm-level strategic initiatives rather than the psychological traits of top executives. The study contributes to the literature on sustainable innovation and behavioral corporate governance by providing evidence from an emerging market context.